Effect Of Feeding Graded Levels of Whole Sugarcane Waste with Or Without Fishmeal and Grasshopper Meal Supplementation in The Diets of Broilers - Adedeji.M. O; Habiba.Z; Duweni.T.; Adeniji. A.A (Zien Journals, 2021)
A total of two hundred and seventy (270) day old broiler chicks were used to evaluate the effect of feeding graded level of whole sugarcane waste with or without fishmeal and grasshopper meal supplementation in the diet of broiler. The diet formulated had three (3) inclusion levels of Whole sugarcane waste (WSW) at 0, 5, 10 %, with animal protein supplementation (fishmeal and grasshopper meal) at 2.5 % The experimental animals were randomly distributed into nine dietary treatments. There were three replicates per treatment with ten birds per replicates. Feed and water were supplied ad-libitum while standard poultry management where strictly followed during the study. Data on different performance parameters such as average daily feed intake, average daily weight gain, feed conversion efficiency and cost of feed where collected. It was a 3×3 factorial experiment in a complete randomized design (CRD). The experiment lasted for a period of (8) weeks. The result showed that the experimental diet had significant effects (P <0.05) on final weight, daily feed intake, weight gain and feed to gain ratio. Supplement interaction showed significant difference on final weight, daily feed intake, and feed to gain ratio. This study showed that broilers fed 5% Whole sugar cane waste supplemented with grasshopper meal had better performance as it gave better growth performance When compared to 10% inclusion level. >
Keywords: sugarcane; supplementation; treatments; ad-libitum